Tobacco Smoking is a Risk Factor for Decline Peak Expiratory Flow Rate in Young Healthy Smokers - Saifullah Shaikh; Rabiya Ali; Hina Moazzam (Aziz Fatimah Medical and Dental College, 2021)
Objective: To compare peak expiratory flow rate among smokers and nonsmokers and to establish a relation between PEFR and smoking. Methodology: A cross-sectional study was conducted at Bahria Medical and Dental College, Karachi from August to October 2020. It was comprised of 151 male smokers and nonsmokers healthy subjects of 20 to 25 years age. After taking ethical approval (ERC 21/2020), hundred and fifty one subjects, who fulfill the inclusion criteria were enrolled in the study. PEFR values were estimated by Wright's Peak flow meter. Data was analyzed by SPSS22. Mean PEFR was compared among smokers and nonsmokers. Association between PEFR and smoking was determined by regression analysis. p-value ?0.05 was considered significant. Results: This study was comprised of 151 male participants. Of total subjects, 49 (32.5%), 102(67.5%) were smokers and nonsmokers respectively. Mean±SD age of the study participant's was 22.74±2.657 years. Smokers have lower PEFR values as compared to nonsmokers (323.94 versus 352.65L/min.), this difference was statistically significant (p-value 0.04). Regression analysis showed the negative association of PEFR with smoking, however, this association was not statistically significant (p-value 0.17). Conclusion: Peak expiratory rate was comparatively lower in smokers than nonsmokers healthy young subjects.